A study on the effect of macroeconomic volatility towards local stock market performance: a case of Kuala Lumpur Composite Index (KLCI) / Rohana Abdullah - Abdullah, Rohana (2006)
This study is conducted to answer the question whether interest rate, consumer price index, money supply and foreign exchange rate give effect to the Kuala Lumpur Composite Index (KLCI)'s price performance. In order to measures the interest rate, the base lending rate is applied in this study, while money supply is measures as M2 in monetary aggregate and foreign exchange rate is Malaysia Ringgit quoted as Singapore Dollar. In addition, consumer price index can be proxy to inflation rate. All those factors are considered as independent variables to test whether these factors are giving effect or influence to the KLCI's price, which represent as dependent variable. All the data are collected in monthly basis from 2000 until 2005 and Multiple Linear Regression Analysis Model will be used. Based on the finding, base lending rate and consumer price index are having negative relationship with KLCI's price. Similar with the theory stated that, interest rate and inflation rate are negative relationship with stock prices. Meanwhile, money supply and foreign exchange rate are having positive relationship with the KLCI's price. Overall, among the variables, foreign exchange rate is the most influence factor to the movement or price of the Kuala Lumpur Composite Index.